2022
DOI: 10.3389/fpubh.2022.816023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Public Awareness of and Attitudes Toward Palliative Care: A Cross-Sectional Analysis of the 2018 HINTS Data

Abstract: BackgroundThe global burden of serious health-related suffering requiring palliative care has been projected to grow significantly by 2060, which indicates the imminent need for integrating palliative care into health systems globally. Moreover, research evidence has been accumulating in support of the earlier adoption of palliative care into the treatment course of serious life-threatening illnesses. However, barriers to earlier access to palliative care still remain, which might be attributable to the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Also, a study in the field of palliative care aimed to examine how personal and interpersonal aspects were associated with individual knowledge of and attitudes towards palliative care. The results identified that it was women who had more favourable attitudes towards palliative care [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, a study in the field of palliative care aimed to examine how personal and interpersonal aspects were associated with individual knowledge of and attitudes towards palliative care. The results identified that it was women who had more favourable attitudes towards palliative care [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serious games – games designed to provide a learning experience – can be a strategic resource for palliative care education and awareness. They are described in the literature as a means to study and improve the health of populations in different areas, such as mental health [ 17 , 18 ]. Since the 1990s, these resources have been used in Palliative Care in education, to work on aspects of interdisciplinary communication and transmission of bad news, as well as to address the issue of advance directives [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used univariate linear regression models to explore factors associated with patients’ perceptions of PC (main outcome of interest). Predictors of interest were identified a priori by the research team 20 , 25 , 26 , 27 and included demographic factors (age, sex, race, ethnicity, importance of spirituality, marital status, education), clinical factors (transplant type, Karnofsky performance status, hematopoietic cell transplant-comorbidity index, disease risk, and presence and severity of graft-versus-host disease), time since transplant, transplant center, region of transplant center, familiarity with PC, knowledge of PC, perceived knowledge of PC, perceptions of PC, unmet PC needs, patient’s belief they will be cured with the transplant, symptom burden, and quality of life (physical and mental health). We assessed for collinearity between predictors using Pearson correlation coefficients and found positive collinearity between knowledge of PC (13-item survey) and perceived knowledge about PC (1 item in familiarity with PC domain) (r = .67, P < .0001).…”
Section: Methodsmentioning
confidence: 99%